SAPO-34 based zeolite coatings for adsorption heat pumps. (15th November 2019) - Calabrese, L.; Bonaccorsi, L.; Bruzzaniti, P.; Proverbio, E.; Freni, A.
Abstract: In this work, at first, an overview on SAPO-34 zeolite coating for adsorption heat pumps is presented, highlighting current quality standard and open technological issues (i.e. the need for good mechanical and hydrothermal stability, high aging stability, etc.). Afterwards, we present an improved formulation of adsorbent composite coatings on aluminum support, having improved thermal and mechanical properties, especially when subjected to an impulsive stress. Specifically, the coated samples were prepared by dip-coating method starting from a water suspension of SAPO-34 zeolite and a hybrid polymer binder. Adhesive and mechanical properties were evaluated by pull-off test confirming the good interaction between metal substrate, filler and matrix. Adsorption equilibrium of water vapor on the adsorbent coating was measured in the range T = 30–150 °C and partial pressure of moisture equal to 11 mbar. It was found that binder does not affect the water adsorption capacity and adsorption rate of the original SAPO-34 zeolite.